PENGGUNAAN METODE CREATIVE PROBLEM SOLVING TERHADAP PEMBELAJARAN PESAWAT SEDERHANA UNTUK PENINGKATAN PEMAHAMAN KONSEP DAN KETERAMPILAN BERPIKIR KREATIF SISWA SEKOLAH DASAR - Yunus, Mardi; Fahyuddin, Fahyuddin; Safiuddin, La Ode (Halu Oleo University)
Abstract. This study aimed to determine the mean score of improvement (N-`gain) in students’ understanding of concepts and creative thinking skill after they received instruction using creative problem-solving method and how significant it was when compared to the improvement made by their cohort who learnt via direct learning method, especially in their learning of simple airplane material. The sample of this research is 68 sixth grade students from elementary school of Integrated Islam Al Qalam Kendari where they are distributed in two parallel classes (VA and VB). The VA class (N = 34) was randomly selected to be the experimental class (get Creative Problem Solving), while the VB class (N = 34) as the control class (get direct instruction). This study was a quasi experiment that using